Students' Abilities in Reading Infographics Text in Junior High Schools - Retnaningtyas, Nina; Damaianti, Vismaia Sabariah; Mulyati, Yeti; Sastromiharjo, Andoyo (Universitas Negeri Makassar, 2024)
Infographic text is a visual text in the form of a combination of images, graphics, illustrations, and typography that serves to facilitate readers in understanding information. Therefore, infographic text is presented with an attractive appearance by increasing the number of illustrations and a little text. The widespread use of infographic text in every aspect of life today requires everyone to have adequate ability to read infographic text. Therefore, in this study the author conducted research on the ability of junior high school students to read infographic texts. The method used in this research is quantitative descriptive method. The object of the research is students of Class VIII of Junior High School in one of the districts in Central Java province. The results showed that the ability to read infographic texts of junior high school students in one of the districts in Central Java still needs to be improved. It can be seen from the low score obtained in doing infographic text questions. There are several efforts that teachers can make to improve students' ability to read infographic texts, namely by increasing visual literacy, improving reading skills, providing knowledge about infographics, and providing practice reading infographic texts.